Flavans with potential anti-inflammatory activities from Zephyranthes candida. Issue 24 (15th December 2016) - Zhan, Guanqun; Zhou, Junfei; Liu, Tingting; Zheng, Guijuan; Aisa, Haji Akber; Yao, Guangmin
Graphical abstract: Abstract: Three new flavans, (2 R, 3 R )-7-methoxy-flavan-3-ol (1 ), (2 S )-7, 3′-dihydroxy-4′-methoxyflavan 3′-O- β -d -glucopyranoside (2 ), (2 S )-7, 3′-dihydroxy-4′-methoxyflavan 7-O- β -d -glucopyranoside (3 ), and one known flavan (4 ) were isolated from the whole plants of Zephyranthes candida (Amaryllidacea). The structures of the new flavans1 –3 were determined by extensive spectroscopic analyses including HRESIMS, NMR, and electronic circular dichroism (ECD), and the absolute configuration of1 was confirmed by single-crystal X-ray diffraction analysis with Cu Kα irradiation. Flavans1 –3 displayed significant inhibitory effects on the LPS-induced NO production in RAW264.7 mouse macrophages with IC50 values of 17.34, 16.14, and 21.52 μM, respectively, suggesting their potentials for anti-inflammatory agents.